Mail order wife - Botko, Huck; Gurland, Andrew; Gurland, Andrew; Yuan, Eugenia; Martinez, Adrian (Distributed by D' Concorde recording corp., 2005)
bachelor looking for a wife agrees to be filmed for a mock documentary as he gets a mail order bride. His new wife is convinced he wants a maid more than anything. A dark comedy about how hard it is to find love, especially from a catalogue.